Expresión yz∨¬y¬z∨¬x¬z
El profesor se sorprenderá mucho al ver tu solución correcta😉
Solución
(y∧z)∨(¬x∧¬z)∨(¬y∧¬z)
(y∧z)∨((¬x)∧(¬z))∨((¬y)∧(¬z))
Tabla de verdad
+---+---+---+--------+
| x | y | z | result |
+===+===+===+========+
| 0 | 0 | 0 | 1 |
+---+---+---+--------+
| 0 | 0 | 1 | 0 |
+---+---+---+--------+
| 0 | 1 | 0 | 1 |
+---+---+---+--------+
| 0 | 1 | 1 | 1 |
+---+---+---+--------+
| 1 | 0 | 0 | 1 |
+---+---+---+--------+
| 1 | 0 | 1 | 0 |
+---+---+---+--------+
| 1 | 1 | 0 | 0 |
+---+---+---+--------+
| 1 | 1 | 1 | 1 |
+---+---+---+--------+
Ya está reducido a FND
(y∧z)∨(¬x∧¬z)∨(¬y∧¬z)
(y∧z)∨((¬x)∧(¬z))∨((¬y)∧(¬z))
(y∧z)∨(¬x∧¬z)∨(¬y∧¬z)
(y∧z)∨((¬x)∧(¬z))∨((¬y)∧(¬z))
(y∨¬z)∧(z∨¬z)∧(y∨¬x∨¬y)∧(y∨¬x∨¬z)∧(y∨¬y∨¬z)∧(z∨¬x∨¬y)∧(z∨¬x∨¬z)∧(z∨¬y∨¬z)
(y∨(¬z))∧(z∨(¬z))∧(y∨(¬x)∨(¬y))∧(y∨(¬x)∨(¬z))∧(y∨(¬y)∨(¬z))∧(z∨(¬x)∨(¬y))∧(z∨(¬x)∨(¬z))∧(z∨(¬y)∨(¬z))
(y∨¬z)∧(z∨¬x∨¬y)